Compassionate eschatology: the future as friend - Grimsrud, Ted; Harding, Michael P. (Wipf and Stock Publishers, 2011)
Intro -- Compassionate Eschatology -- Contributors -- Preface -- part one -- Chapter 1: Biblical Apocalyptic -- Chapter 2: The Language of Warfare in the Book of Revelation -- Chapter 3: Between Babylon and Anathoth -- Chapter 4: Faithful, True, and Violent? -- Chapter 5: Hastening the Day When the Earth Will Burn? -- Chapter 6: Turning the Tables -- Chapter 7: God, Judgment, and Non-Violence -- Chapter 8: The Dragon Lives Still -- part two -- Chapter 9: Is the Apocalypse Inevitable? -- Chapter 10: Redeeming the Entire Universe -- Chapter 11: From Ontology to Iconochrony -- Chapter 12: A Kinder, Gentler Apocalypse? -- Chapter 13: The Final Judgment -- Chapter 14: Orthodox Eschatology and St. Gregory of Nyssa's De vita Moysis -- Chapter 15: Prophecy, End-Times, and American Apocalypse -- Chapter 16: Vincent Van Gogh's Compassionate Eschatology -- Bibliography.